Magnetostratigraphy and Tectonic Rotation of the Eocene-Oligocene Makah and Hoko River Formations, Northwest Washington, USA - Donald R. Prothero; Elizabeth Draus; Casey Burns (International Journal of Geophysics)
The Eocene-Oligocene Makah Formation and subjacent middle Eocene Hoko River Formation of the northwestern Olympic Peninsula, Washington, yield mollusks, crustaceans, foraminifera, and early neocete whales; their age has never been precisely established. We sampled several sections; most samples showed a stable single-component remanence held largely in magnetite and passed a Class I reversal test. The upper Refugian (late Eocene) and lower Zemorrian (early Oligocene) rocks at Baada Point correlate with Chron C13r (33.7–34.7 Ma) and Chron C12r (30–33 Ma). The Ozette Highway section of the Makah Formation spanned the early Refugian to late Refugian, with a sequence that correlates with Chrons C15r-C13r (33.7–35.3 Ma), and a long reversed early Zemorrian section that correlates with Chron C12r (30–33 Ma). The type section of the Hoko River Formation correlates with Chron C18r (40.0–41.2 Ma). The area sampled shows about 45∘ of post-Oligocene counterclockwise tectonic rotation, consistent with results obtained from the Eocene-Oligocene rocks in the region.